X-efficiency and Stock Performance of Hong Kong, Beijing, and Shanghai banks - Choy, Karen Sin Yuen (2015)
This paper investigates the X-efficiency of Hong Kong, Beijing, and Shanghai banks from 2010 to 2014 with its impact on stock return. The data of 10 publicly listed banks in Hong Kong and 14 publicly listed banks in Beijing and Shanghai is obtained for the efficiency estimation, with the use of Stochastic Frontier Analysis. The X-efficiency estimates and other stock return determinants are then regressed against banks’ cumulative annual stock return to examine the relationships through the technique of Generalized Method of Moments (GMM). The empirical results from this study suggest that bank efficiencies of the three regions has deteriorated during 2011, and slowly improved after with slightly different trends. In general, Hong Kong listed banks have been operating more cost efficiently at a level of 73.23%, while Beijing and Shanghai listed banks have lower efficiency estimates of 50% and 50.53% respectively. The GMM results have shown the negative and significant impact that X-efficiencies have on bank stock returns, while other determinants such as scores of diminishing scale efficiency have a positive and significant impact on stock returns.